Impact investor motives influencing the decision to invest in social impact venture - Lehasa, Odifentse Mapula-e (My University, 2021)
Underlying socio-economic challenges; slow economic growth; coupled with the COVID-19 global pandemic, have increased the need for resourcefulness, demonstrating a greater demand for social entrepreneurship innovations, and consequently impact investment capital, across the African continent. The growing need for social entrepreneurship, in combating these socio-economic burdens, has made it essential to understand the reasons why impact investors (the primary funders of social enterprises) decide to invest in social impact ventures, over conventional investments. Therefore, the purpose of this study is to determine the extent to which the decision to invest in a social impact venture is driven primarily by the (i) social impact, (ii) financial return, (ii) social impact and financial dual-return, or (iv) signalling (pseudo altruism) of the investment. This study employed a positivist philosophical paradigm, accompanied by a complementary quantitative research methodology. By means of the convenience and snowball sampling techniques, 78 South African impact investors (from a population of 178) consented to participate in the study, through completing a self-administered online survey. Ultimately, the financial return expected from an impact investment was found to be the most significant determinant of the decision to invest in a social impact venture. The social impact motive was found to have no influence on the impact investor’s investment decision, and the dual-return and signalling motives did not contribute to the findings of this study. The use of financial return as a key decision criterion by impact investors can be attributed to the fact that the majority of these investors (respondents) were investing on behalf of a client, and thus bound by fiduciary duties to seek investment opportunities that preserve or grow their client’s wealth. Using the results of this study as a guide, it is envisaged that social entrepreneurs can better structure their ventures to be more attractive, in terms of both social impact and financial return, to potential impact investors.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Entrepreneurship; Social entrepreneurship; Impact investing; UCTD; SDG-8: Decent work and economic growth